3D Sign Language: The Development of Mobile Learning Application - Jamaluddin, Nurul Irdina; Haizal, Khairul Haziq; Amin, Nuraliah; Mohamed, Juliana (Multidisciplinary Applied Research and Innovation, 2022)
A sign language is no longer foreign nowadays. Especially for an impaired person that wants to communicate. It becomes a need for them to know about the basics of sign language. A platform is needed to learn about sign language, especially in the pandemic phase of Covid-19 which makes it tough for all communities to learn face to face. Thus, there is a lack of the right resources and platforms to learn basic sign language demanding normal people to know and learn. 3D Sign Language application has been developed to help the community in learning a basic sign language with the issue enabling users to learn basic sign languages and basic conversation. ADDIE model used to implement the project. It’s combination of process to get a good product of the application. As a result, an impaired person such as students at school can use this application as well as parents and the community who wants to learn about basic sign language, can learn easily, quickly and fun because this application is built in an attractive interface with 3D animation that makes the application it is more helpful to users.